1974
DOI: 10.2134/agronj1974.00021962006600030025x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Smutgrass Control and Forage Quality Response in Bermudagrass‐Dallisgrass Pastures1

Abstract: Smutgrass (Sporobolus poiretii Roem and Schult.), a prevalent and increasingly serious weed problem in pasture areas of the southeastern United States, cannot be selectively controlled in swards containing desirable forage species with the available recommended procedures. Dallisgrass (Paspalum dilatatum Poir.)‐bermudagrass (Cynodon dactylon (L.) Pers.) pasture swards, the most prevalent type of pastures in our region, were selected for uniform infestation of smutgrass and treated with atrazine [2‐chloro‐4‐(et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…These results differ from those reported in Mississippi 3where 88% control was obtained from atrazine applied at the 4.4 kg/ha rate. Atrazine applied at either 6.7 or 9 kg/ha as a single treatment controlled 81 to 99% of the smutgrass when treatments were made in November 1972, January 1973, or 1974 (Table 1). Atrazine at 4.4 kg/ha rate controlled 84% of the smutgrass when applied in November 1972 but only 40% when the same rate was applied in October of the same year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results differ from those reported in Mississippi 3where 88% control was obtained from atrazine applied at the 4.4 kg/ha rate. Atrazine applied at either 6.7 or 9 kg/ha as a single treatment controlled 81 to 99% of the smutgrass when treatments were made in November 1972, January 1973, or 1974 (Table 1). Atrazine at 4.4 kg/ha rate controlled 84% of the smutgrass when applied in November 1972 but only 40% when the same rate was applied in October of the same year.…”
Section: Resultsmentioning
confidence: 99%
“…There fore, these chemicals would cause undesirable characteristics if applied to home lawns and golf courses. Atrazine and bromacil gave selective smutgrass control when applied to dallisgrass (Paspalum dilatatum Poir) and bermudagrass pastures in Missis sippi (3).…”
Section: Introductionmentioning
confidence: 99%
“…Our primary goal was to demonstrate that defoliation of smutgrass plants and increased stock density could be used to reduce the extent of the smutgrass problem on cattle ranches without disrupting normal management activities. Secondary goals included: 1) Reducing the vigor of smutgrass plants, 2) Comparing the effect of treatments on the number and size of smutgrass plants, 3) Reducing the number of smutgrass plants reaching maturity and producing seed, and 4) Maintaining acceptable body condition and weight gain on grazing animals.…”
Section: About the Projectmentioning
confidence: 99%
“…Ryegrass (Lolium perenne L.) was successfully established by seeding 2 weeks after dalapon application in the fall. Smith et al (17,18) showed that fall applications of atrazine at 4.5 kg/ha or bromacil at 2.2 kg/ha gave at least 83% smutgrass control, while causing 28 and 32% or less injury to dallisgrass (Paspalum dilatatum Poir.) and bermudagrass, respectively, 36 weeks after treatment.…”
Section: Introductionmentioning
confidence: 99%